(untitled) (CAHIERS MAGELLANES-NS, 2024)
Abstract: The current workplace as we know and experience, is increasingly marred and thus characterized by long working hours, stress, exhaustion, unrealistic targets, and a lack of motivation contributing to widespread mental health issues and dissatisfaction among employees. Also, familial expectations, economic pressures, cultural norms, peer pressure, and inadequate policies have decisively contributed to an imbalanced work-life dynamic, particularly affecting millennials and Gen Z who are rejecting the Hustle Culture and redefining the meaning of work. These challenges have been further exacerbated by the fast-paced start-up culture and technological advancements such as AI, which threaten job security in the IT and ITeS industry. Women especially are at the receiving end finding it difficult to manage professional and personal responsibilities with terms like “Mass resignation, Quiet quitting, lazy girl job, No Purpose work, Rage applying, Enculturation, Online fatigue” becoming a frenzy.